Efficacy of sodium oxybate on REM sleep behavior disorder in a patient with narcolepsy type 1. (13th December 2016) - Mayer, Geert
Abstract : Idiopathic REM sleep behavior disorder (iRBD) is a rare disease (0.0038%–0.005%). 1 In patients with narcolepsy type 1 (NT1), symptomatic RBD is a frequent, comorbid disease, ranging from 45% to 61%. 2 iRBD is a premotor stage of neurodegenerative disease. Few patients with narcolepsy develop Alzheimer disease or Parkinson disease. 3 Treatment studies in patients with RBD are rare and have small sample sizes and heterogeneous populations and methods. 4 Sodium oxybate (SO) has been efficacious in 2 patients with iRBD. 5, 6